2017
DOI: 10.1002/jctb.5261
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of molecule imprinted membrane of single enantiomer of amino acid with an innovative strategy and study on its chiral recognition and resolution properties

Abstract: BACKGROUND The molecularly imprinted membranes (MIMs) with high performance are very valuable in the chiral resolution of amino acids. In this work, a novel molecularly imprinted membrane of the single enantiomer of amino acids with graft type was successfully prepared by using an advanced surface imprinting technique. The aminated microfiltration membrane of polysulfone, AMPSF membrane, was first prepared, and so a surface‐initiating system of ‐NH2/S2O8‐ was constituted. In an aqueous solution, the molecules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Hence, the penetrating fluid achieved an enantiomeric excess higher than 82%. Moreover, comparing with the previous method that they used to prepare imprinted membranes, i.e., "pre-graft polymerization and post-imprinting" [150], it was concluded that the present method was more effective and simple, and the obtained membranes revealed a better performance [151].…”
Section: Imprinted Membranesmentioning
confidence: 69%
See 1 more Smart Citation
“…Hence, the penetrating fluid achieved an enantiomeric excess higher than 82%. Moreover, comparing with the previous method that they used to prepare imprinted membranes, i.e., "pre-graft polymerization and post-imprinting" [150], it was concluded that the present method was more effective and simple, and the obtained membranes revealed a better performance [151].…”
Section: Imprinted Membranesmentioning
confidence: 69%
“…The same group successfully prepared a novel grafting-type MIM of a single enantiomer of amino acids by an innovative and advanced surface-imprinting technique of "synchronously graft-polymerizing and molecule imprinting" [151]. Firstly, the aminated microfiltration membrane of polysulfone, AMPSF membrane, was prepared creating a surface-initiating system of -NH 2 /S 2 O 8 .…”
Section: Imprinted Membranesmentioning
confidence: 99%
“…In the spectrum of CMPSF membrane, there are two characteristic absorption bands of chloromethyl groups at 1441 and 660 cm −1 , and they are attributed to the in‐plane bending vibration absorption of C─H bond and the stretching vibration of C─Cl bond in the group ─CH 2 Cl, respectively. By contrast, in the spectrum of PSF‐DEA membrane, the two characteristic absorption bands of chloromethyl groups have weakened greatly.…”
Section: Resultsmentioning
confidence: 99%
“…In order to develop grafting‐type functional composite membranes, it is a promising method to constitute surface‐initiating systems at the interface between the substrate membranes and the solutions containing functional monomers, and the graft polymerization of the functional monomers can be conducted under mild conditions, resulting in the functional composite membranes with high performance. Previously, we designed and constituted a surface‐initiating system of primary amine group/persulfate (─NH 2 /S 2 O 8 2− ) at the interface between chloromethylated polysulfone (CMPSF) microfiltration membranes and aqueous solution, and the graft polymerizations of methacrylic acid (MAA) and dimethylaminoethyl methacrylate (DMAEMA) were successfully realized on the surface of CMPSF membrane as substrate membrane . The obtained grafting‐type composite membranes were used for the separations of alkaloids and acidic amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…Chloromethylated polysulfone (CMPSF) was self‐synthesized and its chlorine content or the content of chloromethyl group was 2 mmol g −1 . Then CMPSF microfiltration membrane with a thickness of 200 µm and with a bore diameter range of 0.1‐1 µm was prepared by the method of immersion‐precipitation phase transformation . 3‐Hydroxy‐N,N‐diethylaniline (HDEA) was Aladdin's reagent, and purchased from Shanghai Aladdin Bio‐Chem Technology Co., Ltd (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%